2010
DOI: 10.1258/jrsm.2010.100307
|View full text |Cite
|
Sign up to set email alerts
|

External aortic root support for Marfan syndrome

Abstract: We have read the interesting article by Pepper and colleagues 1 about their experience on the external support of the aortic root in Marfan syndrome. This is a good contribution to the expanding literature about Marfan syndrome; however, there are few facts that should be clarified.First of all, 66 patients have been removed from the analysis for the comparison of the groups due to previous operations or re-operations. Why? Reoperation in the Marfan patients is an important fact that should be kept in mind in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Finally, most of the Scorzonera species are well‐known traditional remedies in different countries. There are several records to show the usage of the genus as wound healer, [10] analgesic, [11] hypolipidemic, [12] diuretic, [13] and antidiabetic [14] in Turkish folk medicine. Previous studies on the genus revealed the presence of different secondary metabolites such as terpenoids, flavonoids, phenolic acid esters, bibenzyls, coumarins, dihydroisocoumarins, and various bioactivities such as anti‐inflammatory, antioxidant, antimicrobial, antidiabetic, hepatoprotective, wound healing, and analgesic activities [15–20] .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, most of the Scorzonera species are well‐known traditional remedies in different countries. There are several records to show the usage of the genus as wound healer, [10] analgesic, [11] hypolipidemic, [12] diuretic, [13] and antidiabetic [14] in Turkish folk medicine. Previous studies on the genus revealed the presence of different secondary metabolites such as terpenoids, flavonoids, phenolic acid esters, bibenzyls, coumarins, dihydroisocoumarins, and various bioactivities such as anti‐inflammatory, antioxidant, antimicrobial, antidiabetic, hepatoprotective, wound healing, and analgesic activities [15–20] .…”
Section: Introductionmentioning
confidence: 99%